Evaluation of MMR Vaccination and Autism Link - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A retrospective cohort study of autism in all children born in Denmark from January 1991 through December 1998 and those receiving measles, mumps, and rubella (MMR) vaccination is reported from the Danish Epidemiology Science Center, Aarhus, Denmark.